The Role of Social Network Marketing on Consumer Engagement and Purchase Intention: A Review - Kai, Yuan; Valencia, Manuelita G. (International Journal of Global Economics and Management, 2024)
This paper explores the influence of social network marketing on consumer engagement and purchase intentions. As a vital component of modern marketing, social network marketing leverages social media platforms to promote products and services, becoming a primary strategy for businesses to attract and interact with consumers. Through a literature review and case studies, this paper delves into the mechanisms by which social network marketing enhances consumer engagement, including the roles of social interaction, user-generated content, and social proof. Additionally, it examines how personalized marketing strategies and social recommendations within social network marketing influence consumers’ purchase intentions. Finally, the paper discusses the limitations of current research and proposes future research directions to deepen the understanding of social network marketing’s impact.